Factors affecting pre-service teachers’ intention to integrate technologies into their future classrooms : A quantitative study - Myllykangas, Meri (My University, 2023)
This MA thesis set out to examine pre-service teachers and their views about technologies in their future classrooms. The thesis studies five factors – technology adoption intention, technology self-efficacy, attitudes toward technology, perceived ease of use of technology, and perceived barriers of technology. The participants were university students aiming to be teachers in the future and the data was gathered by using a Likert-scale questionnaire. Both the questionnaire and the framework used in this thesis were created by Li, Li, and Franklin (2016). This thesis made use of correlation analysis when looking into the connections between the five variables. The present thesis also examined the distribution of the answers and determined three questionnaire items where the answers were the least distributed and three where they were the most distributed, by comparing the percentages each option had received in these items. The results showed that all the variables correlated with each other, except for perceived barriers of technology which only correlated with technology adoption intention and not the other variables. The items that the participants had similar opinions about were about integrating technologies to their future classrooms, technologies being easy to learn and technologies being a helpful tool in the classroom. The items that the participants had differing opinions about were related to having enough time to integrate technologies into their teaching and learning technologies faster than one’s peers. The results indicate that attitudes toward technology is the variable that affects the pre-service teachers’ technology adoption intention the most, and that teachers are positive about integrating technologies into their classrooms but also feel like they do not have enough time either inside or outside classroom to do so properly.
Keywords: classroom technologies, technology integration, pre-service teachers, technologies in teaching